Quantitative phytochemical and heavy metal estimation of Mesua ferrea flowers and Argyreia speciosa leaves - Sahu Alakh N.; Hemalatha S.; Sairam K. (My University, 2025)
Mesua ferrea Linn. belongs to the family Clusiaceae. The flowers have been cream coloured, ebracteate, pedicellate, pedicel short and axillary. The plant Argyreia speciosa Sweet belongs to the family Convulvulaceae. It is a woody climber. Both the plant parts have been authenticated and identified taxonomically. Defattion of flower and leaves have been done by light petroleum ether 40- 60 and then extracted with ethanol by soxhlet extraction method. Gallic acid has been taken as reference standard for total phenolic estimation. The total phenolic in the ethanolic extract of MF and AS equivalent to gallic acid has been found to be 10.12 and 14.72 mg per gram of dry weight extract respectively. Tannic acid has been taken as reference standard for total tannin estimation. The total tannin in the ethanolic extract of MF and AS equivalent to tannic acid has been found to be 8.75 and 11.25 mg per gram of dry weight extract respectively. Rutin has been used as reference standard for flavonoid and flavonol estimation. The total flavonoid content have been found to be 23 ± 1.37 and 30 ± 0.52 mg / gm plant extract in rutin equivalent respectively. The total flavonol content have been found to be 0.49 ± 0.03 and 3.60 ± 0.25 mg / gm plant extract in rutin equivalent respectively. The saponin content of MF have been 98.75 mg/g and AS have been 7.70 mg/g. Heavy metal estimation has been done by inductively coupled plasma optical emission spectrometer. The heavy metals content of MF have been Cd - 0.001 mg/L, Cr - 0.021 mg/L, Ni - 0.012 mg/L, and Pb - 0.010 mg/L and of AS have been Cd - 0.000 mg/L, Cr - 0.013 mg/L, Ni - 0.021 mg/L, and Pb - 0.011 mg/L.